Evaluation of the drug‐drug interaction potential of treosulfan using a physiologically‐based pharmacokinetic modelling approach. Issue 4 (13th October 2021) - Schaller, Stephan; Martins, Frederico S.; Balazki, Pavel; Böhm, Sonja; Baumgart, Joachim; Hilger, Ralf A.; Beelen, Dietrich W.; Hemmelmann, Claudia; Ring, Arne
Abstract : Aims: The aim of this work is the development of a mechanistic physiologically‐based pharmacokinetic (PBPK) model using in vitro to in vivo extrapolation to conduct a drug‐drug interaction (DDI) assessment of treosulfan against two cytochrome p450 (CYP) isoenzymes and P‐glycoprotein (P‐gp) substrates. Methods: A PBPK model for treosulfan was developed de novo based on literature and unpublished clinical data. The PBPK DDI analysis was conducted using the U.S. Food and Drug Administration (FDA) DDI index drugs (probe substrates) midazolam, omeprazole and digoxin for CYP3A4, CYP2C19 and P‐gp, respectively. Qualified and documented PBPK models of the probe substrates have been adopted from an open‐source online model database. Results: The PBPK model for treosulfan, based on both in vitro and in vivo data, was able to predict the plasma concentration‐time profiles and exposure levels of treosulfan applied for a standard conditioning treatment. Medium and low potentials for DDI on CYP3A4 (maximum area under the concentration‐time curve ratio (AUCRmax = 2.23) and CYP2C19 (AUCRmax = 1.6) were predicted, respectively, using probe substrates midazolam and omeprazole. Treosulfan was not predicted to cause a DDI on P‐gp. Conclusion: Medicinal products with a narrow therapeutic index (eg, digoxin) that are substrates for CYP3A4, CYP2C19 or P‐gp should not be given during treatment with treosulfan. However, considering the comprehensive treosulfan‐based conditioning treatment schedule and the respective pharmacokinetic properties of the concomitantly used drugs (eg, half‐life), the potential for interaction on all evaluated mechanisms would be low (AUCR < 1.25), if concomitantly administered drugs are dosed either 2 hours before or 8 hours after the 2‐hour intravenous infusion of treosulfan.